Impoliteness Strategies in Trevor Noah’s Afraid of The Dark Stand-up Comedy Show - Aulia Hafisa; Sharifah Hanidar (Universitas Gadjah Mada, 2020)
This research focuses on identifying the impoliteness strategies and explaining the purposes of the most frequently used strategy in Afraid of the Dark stand-up comedy show performed by Trevor Noah. The data of this research are Trevor Noah’s utterances which contains impoliteness strategies. The analysis was based on the impoliteness strategies theory proposed by Jonathan Culpeper (1996). The result of this research shows that Trevor Noah uses 105 instances of impoliteness strategies which cover all five types of strategies proposed by Culpeper; bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm or mock politeness, and withhold politeness. Based on the findings, negative impoliteness is found to be the most frequently used strategy. It occurs 42 times or with a percentage of 40% of the whole data. This high frequency of negative impoliteness strategy is used to entertain the audience. Trevor Noah mostly used ‘condescend, scorn, or ridicule’ sub-strategies of negative impoliteness intended to amuse and entertain the audience and also to induce laughter when hearing one being ridiculed or disparaged.